Alternative Raw Materials for Animal Feed - A R Alimon (Indonesian Center for Animal Research and Development, 2009)
The increase in world fuel prices in the last few years has charged the global animal feedstuffs. In Malaysia, the feed industry is dependent on the importation of corn and soybean meal as the poultry and swine industries are almost totally based on corn soya bean meal diets. However, there are many byproducts and coproducts available in Malaysia as alternatives to corn or soy bean. Since Malaysia has more than 4 million hectares of oil palm plantation and after processing for the oil, large quantities of several byproducts are produced. This paper describes several available byproducts and co products in Malaysia, their nutritive value and their problems. Key words: Byproducts, non conventional feed, Malaysia